Potential of using refined red palm olein in carrot cake - Seiza Ahmad Alyas; Aminah Abdullah; Nor Aini Idris (Universiti Kebangsaan Malaysia, 2002)
The possibility of using refined red palm olein in carrot cake was studied. Cakes were prepared using refined red palm olein (Carotino®) by itself and in combination with other vegetable oils. Five cake formulations were developed. Formulation A containing 100% soya bean oil (SBO), formulation B with 100% palm olein (POO), formulation C using 100% refined red palm olein (RRPO). Formulation D is similar to C, but with less amount of sugar while formulation E contained all three types of oils blended at a ratio of 1/3:1/3: 1/3. The cake samples were subjected to sensory evaluation to determine the acceptability of the cake. Specific volume and texture of 5 cake formulations were determined using rapeseed displacement and texture meter respectively. The results of the study showed that there were significant differences (p<0.05) in sensory rating for texture, sweetness, oiliness and overall acceptability for samples A, C and D. In term of colour there was no significant difference. For overall acceptability rating, cake B was rated the most acceptable (4.2) followed by cake C and A (3.7), However there was no significant difference between cake B and cake C. Cake E have the highest specific volume (1.50 cm3 g-1) followed by B (1.47 cm3g-1) and A (1.44 cm3 g-1). ln term of hardness cake C was softest and there was inverse relationship (r=-0.98) between instrumental texture measurement and texture evaluated by sensory test.